Golgi inCOGnito: From vesicle tethering to human disease - D'Souza, Zinia; Taher, Farhana S.; Lupashin, Vladimir V. (Biochimica et biophysica acta. General subjects, 2020)
The Conserved Oligomeric Golgi (COG) complex, a multi-subunit vesicle tethering complex of the CATCHR (Complexes Associated with Tethering Containing Helical Rods) family, controls several aspects of cellular homeostasis by orchestrating retrograde vesicle traffic within the Golgi. The COG complex interacts with all key players regulating intra-Golgi trafficking, namely SNAREs, SNARE-interacting proteins, Rabs, coiled-coil tethers, and vesicular coats. In cells, COG deficiencies result in the accumulation of non-tethered COG-complex dependent (CCD) vesicles, dramatic morphological and functional abnormalities of the Golgi and endosomes, severe defects in N- and O- glycosylation, Golgi retrograde trafficking, sorting and protein secretion. In humans, COG mutations lead to severe multi-systemic diseases known as COG-Congenital Disorders of Glycosylation (COG-CDG). In this report, we review the current knowledge of the COG complex and analyze COG-related trafficking and glycosylation defects in COG-CDG patients. [Display omitted] •Intracellular membrane trafficking and glycosylation.•COG complex structure and functions.•COG-CDGs: clinical presentation and molecular analysis.